The Parkinson's Journey: From Drug Discovery to Treatment of Early and Advancing Disease - Rizzo, Toni (MD Conference Express, 2014)
Efforts to find a treatment for Parkinson's disease (PD) began in the mid-1950s with the discovery of levodopa (L-dopa). Since then, advancements in treatment have included a variety of different modes of L-dopa administration as well as the development of other medical therapies, continuous infusions, and deep brain stimulation. This discusses the L-dopa story and treatment strategies for early and late PD.